AKULTURASI BUDAYA TIMUR TENGAH DI INDONESIA (Kedatangan Islam dan Pengaruh Budaya) - Ahans Mahabie (MAMBA'UL 'ULUM, 2020)
From the history of Islamic conquest to various parts of the world, Indonesia was one of the countries that was visited on the journey and the struggle to spread the monotheistic religion. With the entry of Islam into Indonesia, there was an encounter with all forms of Middle Eastern / Arabic culture, especially Islam with the archipelago, and naturally the encounter experienced acculturation with the culture in Indonesia. Indonesia as a country also has its own indigenous culture. Portraits of indigenous Indonesian culture can now be found in inland-inland areas such as the Tengger people found on Sukapura on the slopes of Mount Bromo near Tasar Malang, Samin communities in Blora, Central Java, Baduwi communities in southern Banten, Kubu communities in southern Sumatra and Jambi, Baliage communities in Tenganan Pegringsing Karang Asem in Bali, and the Toraja community in Central Sulawesi, the Dayak tribe consisting of Oloot, Olonaju, and Manyansiyung in the interior of Borneo, and the Asmat tribe in Irian Jaya. All of them still hold the original culture with several forms such as animism, dynamism, veteism, and shammanism. The arrival of Islam to Indonesia in the First Century H / VII-VIII M resulted in this nation experiencing cultural acculturation between Middle Eastern culture and Indonesian culture. The evidence of acculturation can be felt in several aspects, including language, literature, arts and education.